Author Correction: Origin of large plasticity and multiscale effects in iron-based metallic glasses - Baran Sarac (Nature Portfolio, 2018)
The authors became aware of a mistake in the original version of this Article. Specifically, where discussing the Curie temperature of the amorphous phase, T c, in the ‘Thermal characterization’ section of the Results and in Fig. 2, the authors should have been discussing the Curie temperature of the magnetic crystalline phases T’ c. While the Curie temperature of the glass is lower than previously reported, this error does not affect the original discussion or conclusions of the Article. The authors apologize for the confusion caused by this mistake. In addition to this, there were errors in some of the equations in the main text, and the glass composition. A number of changes have been made in both the PDF and HTML versions of the Article to reflect these errors. A full list of these changes is available online.